2007
DOI: 10.1136/oem.2007.032896
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of particulate pollution and cold temperature on cardiorespiratory mortality in Scotland

Abstract: Objectives: To determine whether the effect of black smoke on cardiorespiratory mortality is modified by cold temperatures. Methods: Poisson regression models were used to investigate the relationship between lagged black smoke concentration and daily mortality, and whether the effect of black smoke on mortality was modified by cold temperature for three Scottish cities from January 1981 to December 2001.Main results: For all-cause respiratory and noncardiorespiratory mortality, there was a significant associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 33 publications
(34 reference statements)
5
40
0
3
Order By: Relevance
“…In Italy, an effect of PM10 on respiratory mortality was found only for temperatures above the 50th percentile compared to no effect on days with a temperature below the 50th percentile [55]. The study of CARDER et al [79], carried out in Scotland, instead found a positive interaction between cold temperatures and black smoke concentrations on respiratory mortality. Other European studies analysed total mortality; they were focused on specific heatwave episodes [64,[66][67][68][69] or on both warm and cold periods [70] and provided evidence of a significant interaction between high temperature and pollutants, mainly ozone.…”
Section: Synergy (Effect Modification) Of Air Pollution and Temperatumentioning
confidence: 64%
See 2 more Smart Citations
“…In Italy, an effect of PM10 on respiratory mortality was found only for temperatures above the 50th percentile compared to no effect on days with a temperature below the 50th percentile [55]. The study of CARDER et al [79], carried out in Scotland, instead found a positive interaction between cold temperatures and black smoke concentrations on respiratory mortality. Other European studies analysed total mortality; they were focused on specific heatwave episodes [64,[66][67][68][69] or on both warm and cold periods [70] and provided evidence of a significant interaction between high temperature and pollutants, mainly ozone.…”
Section: Synergy (Effect Modification) Of Air Pollution and Temperatumentioning
confidence: 64%
“…among those most susceptible, has the consequence of a larger pool of susceptible people at risk of air pollution effects the following summer [70,124,127]. To explain the interaction between pollutant and low temperature [79], a hypothesised mechanism is that the cold-related impairment of respiratory mucociliary function may inhibit the clearance of pollutants [107,108].…”
Section: Mechanisms and Vulnerable Subgroupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Se debe tener en cuenta que determinadas situaciones meteorológicas relacionadas con los extre mos térmicos favorecen la presencia de estos contaminantes, sobre todo en las gran des urbes debido principalmente al trans porte y a las actividades industriales. Algu nos autores incluso se cuestionan si esto debe tener implicaciones en los estándares de calidad del aire, estableciendo medidas para disminuir la máxima concentración permitida cuando se prevén situaciones peligrosas 45 .…”
Section: Aspectos Que Convendría Incluir En Los Nuevos Planes De Prevunclassified
“…The combined effect of urban heat islands and heatwaves may also increase the risk for potential heat-related illness for the individuals living in the urban zone (Basara et al 2010). The possibility of interactions between cold temperature and air pollutants in terms of their effect on cardiorespiratory mortality and whether this relation varies according to season has been investigated (Roberts 2004;Carder et al 2008).…”
Section: Physical and Chemical Weathermentioning
confidence: 99%